Comparison of the accuracy of body temperature measurements with temporal artery thermometer and axillary mercury thermometer in term newborns - Markus Gunawan; Soetjiningsih Soetjiningsih; I Made Kardana (Indonesian Pediatric Society Publishing House, 2010)
Abstract Background Rectal mercury thermometer (RT) has been considered to be a clinical thermometer that measures body temperature close to core temperature. Unfortunately it is relatively uncomfortable to the patient. Axillary mercury thermometer (AT) is a relatively safe method, but time consuming and its accuracy has been questioned. Temporal artery thermometer (TAT) is relatively a new method that can measure body temperature faster, and well tolerated. Objective To compare the accuracy of temperature measurement between TAT and AT in neonates. Methods Cross-sectional analytic study was conducted at Neonatology Division at Sanglah Hospital, Denpasar. Every healthy term newborn who met the criteria were measured their body temperature by using three kinds of thermometer consecutively. The limits of agreement, correlation and linear regression analysis were done to find TAT and AT's agreement and correlation to RT. Results One hundred and thirty four newborns were enrolled in this study. TAT had a better agreement to RT with the mean 􀁇􀁌􀁉􀁉􀁈􀁕􀁈􀁑􀁆􀁈􀀃􀁒􀁉􀀃􀀐􀀓􀀑􀀓􀀔􀂞􀀦􀀃􀁚􀁌􀁗􀁋􀀃􀀕􀀃􀀶􀀧􀀃􀁏􀁒􀁚􀁈􀁕􀀃􀁏􀁌􀁐􀁌􀁗􀀃􀁒􀁉􀀃􀀐􀀓􀀑􀀕􀀙􀂞􀀦􀀃􀁄􀁑􀁇􀀃􀁘􀁓􀁓􀁈􀁕􀀃 􀁏􀁌􀁐􀁌􀁗􀀃􀁒􀁉􀀃􀀓􀀑􀀕􀀖􀂞􀀦􀀏􀀃􀁆􀁒􀁐􀁓􀁄􀁕􀁈􀁇􀀃􀁗􀁒􀀃􀁄􀁊􀁕􀁈􀁈􀁐􀁈􀁑􀁗􀀃􀁅􀁈􀁗􀁚􀁈􀁈􀁑􀀃􀀤􀀷􀀃􀁄􀁑􀁇􀀃􀀵􀀷􀀏􀀃􀁚􀁌􀁗􀁋􀀃 􀁐􀁈􀁄􀁑􀀃􀁇􀁌􀁉􀁉􀁈􀁕􀁈􀁑􀁆􀁈􀀃􀀐􀀓􀀑􀀖􀀘􀂞􀀦􀀏􀀃􀀕􀀃􀀶􀀧􀀃􀁏􀁒􀁚􀁈􀁕􀀃􀁏􀁌􀁐􀁌􀁗􀀃􀀐􀀓􀀑􀀚􀀓􀂞􀀦􀀃􀁄􀁑􀁇􀀃􀁘􀁓􀁓􀁈􀁕􀀃􀁏􀁌􀁐􀁌􀁗􀀃 􀁒􀁉􀀃􀀓􀀑􀀓􀀓􀂞􀀦􀀑􀀃􀀷􀁋􀁈􀁕􀁈􀀃􀁚􀁄􀁖􀀃􀁄􀀃􀁖􀁌􀁊􀁑􀁌􀁉􀁌􀁆􀁄􀁑􀁗􀀃􀁏􀁌􀁑􀁈􀁄􀁕􀀃􀁄􀁖􀁖􀁒􀁆􀁌􀁄􀁗􀁌􀁒􀁑􀀃􀁅􀁈􀁗􀁚􀁈􀁈􀁑􀀃􀀷􀀤􀀷􀀃 and RT with correlation coefficient 􀁕􀀃􀀠􀀃􀀓􀀑􀀛􀀚􀀃􀀋􀁓􀀟􀀓􀀑􀀓􀀓􀀔􀀌􀀏􀀃􀁌􀁑􀁗􀁈􀁕􀁆􀁈􀁓􀁗􀀃 􀀓􀀑􀀜􀀛􀀚􀀃􀁄􀁑􀁇􀀃􀁖􀁏􀁒􀁓􀁈􀀃􀀓􀀑􀀘􀀓􀀜􀀑􀀃􀀷􀁋􀁈􀀃􀁏􀁌􀁑􀁈􀁄􀁕􀀃􀁄􀁖􀁖􀁒􀁆􀁌􀁄􀁗􀁌􀁒􀁑􀀃􀁅􀁈􀁗􀁚􀁈􀁈􀁑􀀃􀀤􀀷􀀃􀁄􀁑􀁇􀀃􀀵􀀷􀀃 􀁖􀁋􀁒􀁚􀁈􀁇􀀃􀁗􀁋􀁈􀀃􀁆􀁒􀁕􀁕􀁈􀁏􀁄􀁗􀁌􀁒􀁑􀀃􀁆􀁒􀁈􀁉􀁉􀁌􀁆􀁌􀁈􀁑􀁗􀀃􀁕􀀃􀀠􀀃􀀓􀀑􀀚􀀙􀀃􀀋􀁓􀀟􀀓􀀑􀀓􀀓􀀔􀀌􀀏􀀃􀁌􀁑􀁗􀁈􀁕􀁆􀁈􀁓􀁗􀀃 􀀔􀀓􀀏􀀕􀀚􀀔􀀃􀁇􀁄􀁑􀀃􀁖􀁏􀁒􀁓􀁈􀀃􀀓􀀏􀀚􀀖􀀓􀀑 Conclusion TAT is more accurate than AT for body temperature measurement in the healthy term newborns. [Paediatr Indones. 2010;50:67-72].